Application and Effect Evaluation of Remote Sensing Technology in the Monitoring of Water Pollution - Gao, Hanbo (Transactions on Environment, Energy and Earth Sciences, 2024)
Remote sensing technology has shown significant advantages in water pollution monitoring, which can achieve large-scale and real-time water quality monitoring. This paper introduces the remote sensing technology mainly used in water pollution monitoring and analyzes the application cases of different polluted waters. Remote sensing technology mainly includes optical, thermal infrared, and radar remote sensing. Optical remote sensing monitors the concentration and distribution of pollutants by analyzing the spectral reflection characteristics of water bodies; Thermal infrared remote sensing detects thermal pollution according to the change of water temperature; Radar remote sensing uses electromagnetic wave reflection to identify oil pollution, water level changes and other information, which is not limited by weather conditions. It is suitable for water pollution monitoring in cloudy and rainy areas. At present, remote sensing technology has been successfully applied in different water areas, such as industrial pollution, agricultural non-point source pollution and domestic sewage pollution. Remote sensing technology can quickly identify pollution sources and monitor the diffusion range of pollutants, providing scientific basis for environmental protection departments and supporting environmental protection decision-making. However, some limitations exist, such as insufficient accuracy and weather influence. In the future, it is necessary to optimize the algorithm and sensors further to improve the ability to monitor trace pollutants to better protect the water environment.